(untitled) (Journal of the College of Basic Education, 2023)
The subject of my research is the Prophet of God, Shuaib, peace be upon him, and his people in the Holy Qur’an. Perhaps a questioner will ask: What will you add in your research to what the predecessors and successors have brought? So I say: The Holy Qur’an is the immortal Book of God, a banquet of knowledge, wisdom and character. It is not created, its wonders never end, and its treasures never end, and its reciter ponders over its surahs in every reading, but for its verses he gains what he did not achieve in the previous reading, and this is one of the secrets of his miraculousness, and may God have mercy on him. Exalted be He who said (if the servant was given an alif for each letter of the Qur’an, then he would not have reached the end of what God entrusted in a verse of His Book, because it is the word of God, and His speech is His attribute, and just as God has no end, so there is no end to understanding His words, but each understands according to what God opens On his heart, and the word of God is not created, and it does not reach the end of his understanding, so they are the speaker of his creation ().The Holy Qur’an is replete with lessons and lessons, from that the Prophet of God, Shuaib, may God’s prayers be upon him, sent it to a people of debt who disbelieved in God the Great, the Beneficent, and His messengers and the Last Day, and used their material strength to fight God, may God bless him and grant him peace, with what God gave them of blessings, but they began to underestimate people, so they took a lot and paid with a little.